BIOCHAR AS A TOOL OF ENVIRONMENTAL BIOTECHNOLOGY (Experimental biology, 2026)
Current review examines the application of biochar as both a soil amendment and a carrier for microbial cells aimed at addressing challenges in environmental biotechnology. Furthermore, the review describes methods for producing biochar with tailored physicochemical properties, mechanisms of its interaction with organic (pesticides) and inorganic (heavy metals) contaminants, and the potential environmental risks associated with its application. Particular attention is given to the mechanisms of microbial cell immobilization on the biochar surface, their interactions with the carbon matrix, and the potential of such biochar–microbe complexes for soil remediation. The review consolidates and advances current knowledge on the use of biochar-immobilized microorganisms for restoring soil structural characteristics and enhancing its fertility.Improving the efficiency of phytoremediation is a strategically important research objective. To improve plant biomass yield, increase the effectiveness of remediation technologies, and accelerate plant adaptability, biochar is considered a promising tool for enhancing both bio- and phytoremediation processes. Biochar is produced through the thermal decomposition of plant or animal residues under anaerobic or low-oxygen conditions. Its positive impact on soil properties and plant growth is attributed to the presence of minerals (K, Ca, P, Na, Mg, etc.), which help neutralize soil acidity, reduce abiotic stress, and stimulate plant development. Furthermore, biochar exhibits strong sorption capacity for toxic elements, thereby reducing their mobility, bioavailability, and phyto- and ecotoxicity. In practical applications, biochar is presented as an innovative approach for mitigating soil contamination.The aim of the current study is to broaden the understanding of up-to-date methods for microbial immobilization on biochar to improve soil properties, enhance fertility, and effectively stabilize both organic and inorganic contaminants in the environmental matrices.
Keywords: biochar; pyrolysis; soil; potentially toxic elements; persistent organic pollutants